2017
DOI: 10.1071/rj16077
|View full text |Cite
|
Sign up to set email alerts
|

Managing rain-filled wetlands for carbon sequestration: a synthesis

Abstract: Abstract. Global acknowledgement of climate change and its predicted environmental consequences has created a need for practical management techniques that increase a landscape's ability to capture and store atmospheric carbon (C). Globally, wetlands sequester disproportionally more C per unit surface area than many other components of the landscape. However, wetlands vary in their capacity to store C and regulate greenhouse gas emissions. Hydrology, in particular, is a critical driver of wetland C capture and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Based on these premises, installing fences could reduce aquatic GHG emissions from farm dams while improving agricultural productivity and biodiversity. Previous studies have already shown that excluding livestock and reducing grazing intensity can reduce methane emissions and enhance carbon sequestration and storage of freshwater wetlands (Limpert et al, 2021; Oates et al, 2008; Watkins et al, 2017). Yet, the effects of installing fences (or any other management intervention) on farm dam GHG production remain untested.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these premises, installing fences could reduce aquatic GHG emissions from farm dams while improving agricultural productivity and biodiversity. Previous studies have already shown that excluding livestock and reducing grazing intensity can reduce methane emissions and enhance carbon sequestration and storage of freshwater wetlands (Limpert et al, 2021; Oates et al, 2008; Watkins et al, 2017). Yet, the effects of installing fences (or any other management intervention) on farm dam GHG production remain untested.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there is some well-founded concern that loss of biomass through harvesting can disrupt the essential climatic functions of wetlands, e.g., the long-term storage of CO 2 [110]. C released during the energetic conversion of biomass is part of the global cycle of biogenic C and does not affect the amount of C in circulation.…”
Section: Conclusion: Climate-wetlands-nature Conservationmentioning
confidence: 99%
“…The majority of former ponds was turned into agricultural land, permanent grassland, and forest (Pavelková et al, 2014). As a consequence, degradation of freshwater wetlands occurred either through drainage or desiccation, and their conversion to agricultural use has often led to increased carbon emissions (Nieveen et al, 2005;Brigham et al, 2006;Watkins et al, 2017;Tan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%